Aplikasi E-Commerce: Studi Kasus pada PT Eigl - Rudy, Rudy; H., Nicholas; Fransisca, Fransisca; T., Theodore Silvie (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The cosmetics trend is apparently in line with the fashion trend which is likely to change from time to time. Competition in the cosmetics industry today, coupled with the increasing number of imported cosmetic products on the market require cosmetic companies to continue innovating and taking advantage of opportunities as possible. A very rapid development of Internet opens opportunities for cosmetic companies, especially PT EIGL, to be able to offer products to Internet users. The purpose of this study is to build a prototype e-commerce application, preceded by identifying the odds and the readiness of companies in conducting e-commerce. The methodology used is the analysis of the company's readiness using the preparation analysis of a market opportunity and design application using object-oriented approach. The research results in an e-commerce application that consists of the front-end and content management system. From this study it can be concluded that PT EIGL retains the opportunity to run e-commerce. To facilitate the company in managing e-commerce website a content management system is created in an easy way to operate.